Evaluation of gabapentin administration on neurologic examination in 2 different age groups of healthy cats - Allison DuPont; Natalia Zidan; Lizabeth C. Lueck; Starr Cameron (Journal of Veterinary Internal Medicine)
Abstract Background Gabapentin is often administered PO for preappointment or in‐hospital anxiolysis in cats. A previous study reported mild changes on the neurologic examination after administration. Objectives Investigate the effects of gabapentin on anxiety, sedation, compliance, and neurologic examination in 2 age groups of cats. Animals Thirty‐one young cats and 12 geriatric cats perceived by their owners to be healthy and neurologically normal. Methods Prospective double‐blinded clinical crossover study. Assessment of baseline sedation and anxiety was performed before initial neurologic examinations and after gabapentin administration (100 mg/cat). Assessments were repeated 90 to 120 minutes after administration. Ease of handling pregabapentin and postgabapentin was assessed in the younger cats. All examinations were performed by a board‐certified veterinary neurologist and scoring of examinations was performed by a different, masked board‐certified neurologist. Results Sixteen cats (50%) in the younger cohort and 6 cats (50%) in the geriatric cohort exhibited an increase in their overall neurologic examination score postgabapentin administration, mainly through new or progressive postural reaction deficits and gait changes. Anxiety and sedation scores were significantly changed in the geriatric population (P < .01, P = .004, respectively); however, only sedation scores were significantly increased in the younger cats after gabapentin administration (P = .004). Conclusions and Clinical Importance All study participants showed mild neurologic changes after gabapentin administration, most markedly noted in the geriatric population. Dose reduction of gabapentin for preappointment anxiolysis and neurologic examination in geriatric patients should be considered.